2002
DOI: 10.1074/jbc.m201634200
|View full text |Cite
|
Sign up to set email alerts
|

Functional Characterization of Drosophila melanogaster Peptide O-Xylosyltransferase, the Key Enzyme for Proteoglycan Chain Initiation and Member of the Core 2/I N-Acetylglucosaminyltransferase Family

Abstract: Chondroitin and heparan sulfates are essential players in animal development and are synthesized by a series of glycosyltransferases, the first of which is UDP-␣-D-xylose:proteoglycan core protein ␤-D-xylosyltransferase (EC 2.4.2.26). In the present study, a Drosophila melanogaster gene (CG17771), previously designated as a homologue of core 2 and I ␤1,6-N-acetylglucosaminyltransferases, was shown to encode an active peptide O-xylosyltransferase. A novel coupled assay using matrix-assisted laser desorption ion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
57
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(59 citation statements)
references
References 44 publications
2
57
0
Order By: Relevance
“…3a, in bold). Unlike in mammals, for Drosophila (and putatively for other dipterans) the activity of a CS GalNAc-transferase I (GalNAcT-I) as opposed to an N-acetylglucosaminyl transferase I (GlcNAcT-I) determine the initiation and progression of the chain toward either a CSGAG or HSGAG, respectively (16)(17)(18) (Fig. 3a).…”
Section: The Anopheles Gambiae Gag Biosynthetic Pathway and Cloning Omentioning
confidence: 99%
See 3 more Smart Citations
“…3a, in bold). Unlike in mammals, for Drosophila (and putatively for other dipterans) the activity of a CS GalNAc-transferase I (GalNAcT-I) as opposed to an N-acetylglucosaminyl transferase I (GlcNAcT-I) determine the initiation and progression of the chain toward either a CSGAG or HSGAG, respectively (16)(17)(18) (Fig. 3a).…”
Section: The Anopheles Gambiae Gag Biosynthetic Pathway and Cloning Omentioning
confidence: 99%
“…As with human and Drosophila OXTs, AgOXT1 is a type II transmembrane protein, with a WSC motif glycanbinding domain (GBD) and glycosyltransferase family 14 domains ( Fig. 3 b and c), but lacks the characteristic Asp-Xaa-Asp (DXD) motif present in other family members and is involved in coordination of glycan substrates (16). The functional relevance of the lack of a DXD motif in AgOXT1 is not readily apparent, although it has been shown that nematode OXT, which also lacks this motif, is enzymatically active (15).…”
Section: The Anopheles Gambiae Gag Biosynthetic Pathway and Cloning Omentioning
confidence: 99%
See 2 more Smart Citations
“…Biochemical analysis of GAGs has demonstrated that both Caenorhabditis elegans and Drosophila melanogaster have HS and CS (11,12). Recently, Drosophila peptide O-XylT has been reported to transfer xylose (Xyl) to the syndecan peptide (13). But it is still unknown which Drosophila ␤4GalT works as proteoglycan ␤4GalTI.…”
mentioning
confidence: 99%